Análise das manifestações patológicas no edifício residencial da Casa do Estudante em Palmas-TO através da Matriz GUT de priorização - Santos, Vielka Pereira dos (Universidade Federal do Tocantins, 2020)
This work deals with the study of pathological manifestations found at the student's home in Palmas-TO. Data analysis was performed using the GUT prioritization matrix in order to relate anomalies to their resolution priority. The results showed that the structural elements that present corrosion of the reinforcement must be prioritized as to the degree of risk and intervention. It was also possible to detect problems during the survey in ceramic tiles, infiltrations, in the access ramps in metallic structure, in the painting of the external walls of the building and mold. In order to correct such problems therapies have been suggested. However, it is essential to carry out the intervention with corrective maintenance to repair the problems of the inspected building elements and to provide better conditions of use to the residents and better building security. The cost of corrective maintenance is higher than what is spent on preventive maintenance, the lack of this causes small failures that would be of low cost to increase, compromising the quality and even the safety of the work resulting in a high cost for correction.